Pengaruh Koperasi Sekolah sebagai Media Pembelajaran dalam Meningkatkan Minat Berwirausaha Siswa SMK Negeri 1 Bone - , A. Desi Vio Alvionita; Hamka; Sahiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
A deep understanding of entrepreneurship is needed to address the potential of students who are still hesitant to enter the world of entrepreneurship, despite their significant potential. Lack of knowledge about cooperatives and entrepreneurship, therefore, requires increased student participation.This study employed an ex post facto quantitative method. The sample consisted of eleventh-grade AKL students. Data analysis revealed that 38.5% agreed and 61.5% strongly agreed, out of 26 samples. The t-test analysis yielded a t-count of 5.840 > t-table of 1.7108, with a significance level of 0.000 < 0.05. The results of this study indicate a significant influence of school cooperatives as a learning medium in increasing entrepreneurial interest among eleventh-grade AKL students at SMK Negeri 1 Bone.